Peran Pengurus OSIS Sebagai Kelompok Sosial Formal Group Dalam Memotivasi Belajar Siswa Di Mts As-Syafi’iyyah Gondang Tulungagung - Muchamad Khasan Noto Raharjo (Kampus Akademik Publiser, 2024)
The Intra-School Student Organization (OSIS) is a legal and official social group in the school, which is referred to as a formal social group because it has clear and firm rules. This study examines student council administrators' role as a formal social group in motivating student learning at MTs As-Syafi'iyyah Gondang Tulungagung. The research method used is qualitative research with a phenomenological approach. Data was obtained from observation, interviews, and documentation. The data sources obtained are primary and secondary. For the validity of the data, the researcher checked with the time triangulation method, source triangulation, and technique triangulation. The results of this study are 1) How to form student learning motivation, 2) The role of the student council program in motivating student learning, and 3) The involvement of the role of the student council in motivating student learning. It is hoped that the Student Council, as a formal social group, will be able to motivate student learning at MTs As-Syafi'iyyah Gondang Tulungagung.